"Not Your Average Nerd": Masculinities, Privilege, and Academic Effort at an Elite University. Issue 2 (9th March 2020) - Gruys, Kjerstin; Munsch, Christin L.
Abstract : Research on hybrid masculinity shows that privileged men incorporate aspects of subordinated and/or marginalized masculinities into their gender performances, contributing to the persistence of hegemonic masculinity. This scholarship has centered on white, straight, cisgender, class‐privileged men. Yet, it is reasonable to imagine that not all privileged men enact hybrid masculinities and that at least some less‐privileged men engage in hybrid identity work. Here, we draw on 24 interviews with a diverse group of men attending an elite university, examining their beliefs about contemporary masculinity in relation to academic pursuits . Generally, race‐ and class‐privileged respondents rejected academic effort as unmanly while less‐privileged men unapologetically committed themselves to their academic endeavors. Exceptions to these patterns—privileged men who embraced academic effort and less‐privileged men who rejected it—revealed hybrid identity work attempted by both groups. However, only privileged men were able to successfully hybridize their masculine identities, while less‐privileged men were left straddling competing cultural imperatives without clearly accomplishing either. We discuss the implications of these findings for both individual men and for larger patterns of inequality and offer new theoretical insights regarding how race‐ and class privilege shape men's performances of hegemonic, complicit subordinated, marginalized, and hybrid masculinities.